National Fiber Optic Engineers Conference 2010
DOI: 10.1364/nfoec.2010.jtha46
|View full text |Cite
|
Sign up to set email alerts
|

Designing In-Building Optical Fiber Networks

Abstract: Optical fiber in-building networks carrying wired and wireless services can outperform CAT-5E networks regarding versatility and installation costs. POF-based point-to-point architectures are optimum for small buildings, and (optically routed) SMF-based bus architectures for larger buildings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 2 publications
0
10
0
1
Order By: Relevance
“…For P2MP topologies, the CapEx per room initially decreases as the sharing factor of the common network parts increases, but for larger room numbers it increases again as the average cable and duct length start to dominate [8]. Hence for a small building (such as a residential home) a P2P architecture is attractive, also given its simplicity and easy upgradability.…”
Section: Network Costs Analysis Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For P2MP topologies, the CapEx per room initially decreases as the sharing factor of the common network parts increases, but for larger room numbers it increases again as the average cable and duct length start to dominate [8]. Hence for a small building (such as a residential home) a P2P architecture is attractive, also given its simplicity and easy upgradability.…”
Section: Network Costs Analysis Resultsmentioning
confidence: 99%
“…Next to the transmission aspects, a important aspect is the economics, as there is heavy competition from copper-based solutions such as the popular Cat-5E networks. In previous work [8][9][10], it was shown that POF solutions can be already today cost-competitive with Cat-5E regarding installation costs (CapEx -Capital Expenditure). In this paper we extend this work by taking operational costs (OpEx -Operational Expenditure) into account.…”
Section: Introductionmentioning
confidence: 99%
“…for IP packet routing). The details of our analysis method have been reported in [2] . We have analysed three typical building scenarios: a residential home (single family house, with 3 floors and 4 rooms per floor), office building (10 floors, 50 office rooms per floor), and a multi-dwelling units (MDU) building (apartment building, with 10 floors and 16 living units (LUs) per floor).…”
Section: Optimizing In-building Network Architecturesmentioning
confidence: 99%
“…On the other hand, the polymer optical fibre, such as poly (methyl methacrylate) and perfluorinated graded index polymer optical fibre (PF-GI-POF) are preferred to be used in-building networks due to the fact that it is less brittle and more flexible compared to the silica based fibres. Moreover, this type of fibres are associated with the ease of installation (i.e., ease "do-it-yourself" installation scenario) and low maintenance cost, due to its large core diameter [3]- [4]. As the capacity and coverage are the main concerns in the recent mobile communications, a relay node (RN) can be used for further coverage extension.…”
Section: Introductionmentioning
confidence: 99%